Determining facial biotype based upon phenotypic features through structural equation modeling: a study of three ethnic groups - Bedoya-Rodríguez, Antonio; Osorio-Patiño, Julio César; Tamayo-Cardona, Julián Andrés| (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: the various phenotypic characteristics may be grouped; also, their individual and collective influence may be determined when defining a biotype. Structural equation modeling (SEM) is based on causal relations so that the change in a variable is supposed to produce a change in another variable. This model was used to validate causal relations using different types of mediating variables: masticatory force, transverse measures, dental arches, bizygomatic width, and morphological face height. Methods: this study included 197 preteens between 12 and 14 years of age with dental neutroclusion, distributed like this: 33% mestizos, 35% of African descent, and 32% indigenous. The hypothetical model was statistically tested through structural equation modeling. Results: the model is well fitted to the data since goodness of fit indicators such as RMSEA = 0.078, RMR index magnitude = 0.061, and CIF = 0.988 were within the expected limits. The parameters were significant to a 5%, except for facial index with masticatory force. Factor loads ranged from 0.55 to 0.92 and negative factor loads between the facial index and dental arch transverse measures (–0.60). Conclusion: this model shows that the variable that best correlates with facial biotype is masticatory force (0.82), followed by dental arches relation (0.73), this being a moderate correlation.